Jazz improvisation, analysis, and interpretation: Three performances of "Honeysuckle Rose" by Ella Fitzgerald - Hawley, Laura (University of Ottawa (Canada), 2007)
This thesis develops a framework for analyzing melodic improvisation on a jazz standard in order to explore how the improvisation relates to the original melody and harmony of the song. Using three recorded performances of "Honeysuckle Rose" by Ella Fitzgerald, the analytic method reveals the complex web of melodic and harmonic relationships in her improvisational style and musical craft. The first chapter outlines important terminology and addresses the use of transcription as a tool for analyzing recorded performance. The second chapter explores current practices in jazz analysis and discusses strategies for jazz improvisation. Drawing on the work of prominent jazz analysts (Larson, Kernfeld, Hodson) these chapters lead to the formulation of a three-stage model for analyzing melodic jazz improvisation. The third and fourth chapters present an analysis of Thomas "Fats" Waller's "Honeysuckle Rose," comparing analytic information gleaned from performance transcriptions and the lead-sheet. This analysis illustrates the utility of a model that allows the analyst to simultaneously consider aspects of form, melody, and harmony.
Keywords: Music.